2017
DOI: 10.1002/jcb.26425
|View full text |Cite
|
Sign up to set email alerts
|

SNP mutations occurring in thyroid hormone receptor influenced individual susceptibility to triiodothyronine: Molecular dynamics and site‐directed mutagenesis approaches

Abstract: The increasing evidences have suggested that expression of single nucleotide polymorphisms (SNP) coded thyroid hormone receptors (THR) generally are associated with individual susceptibility to chemicals. In the present research, multiple molecular dynamics simulations on four SNP mutants (G332R, T337Δ, G345R, and G347E) were performed to investigate the structural and dynamical altering, which could lead to a binding capability variation to triiodothyronine (T3). It proved the structures of two SNP mutants (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Therefore, our present case may have the rs225104 TT genotype or rs225015 GG genotypes in DIO2 or homozygous UGT1A1*28 variant. Liu et al suggested single nucleotide polymorphisms (SNP) mutations coded in thyroid hormone receptor (THR) influenced individual susceptibility to triiodothyronine [25]. Therefore, the balance of thyroid hormones in human is affected by multiple gene loci and gene polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our present case may have the rs225104 TT genotype or rs225015 GG genotypes in DIO2 or homozygous UGT1A1*28 variant. Liu et al suggested single nucleotide polymorphisms (SNP) mutations coded in thyroid hormone receptor (THR) influenced individual susceptibility to triiodothyronine [25]. Therefore, the balance of thyroid hormones in human is affected by multiple gene loci and gene polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in response to T 3 supplementation have been shown in various strains of chickens [112]. One promising study looking at susceptibility to T 3 used molecular modeling combined with site-directed mutagenesis to investigate mutations in the thyroid hormone receptors that could influence T 3 binding [113]. This study is a step in the right direction towards understanding differences in susceptibility to thyroid disruption.…”
Section: Evidence For Differential Susceptibility To Endocrine-disrupting Chemicalsmentioning
confidence: 99%